2021
DOI: 10.3390/md19020082
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxy p-Terphenyls from a Mangrove Endophytic Fungus Aspergillus candidus LDJ-5

Abstract: Six undescribed polyhydroxy p-terphenyls, namely asperterphenyllins A–F, were isolated from an endophytic fungus Aspergillus candidus LDJ-5. Their structures were determined by NMR and MS data. Differing from the previously reported p-terphenyls, asperterphenyllin A represents the first p-terphenyl dimer connected by a C-C bond. Asperterphenyllin A displayed anti-influenza virus A (H1N1) activity and protein tyrosine phosphatase 1B (PTP1B) inhibitory activity with IC50 values of 53 μM and 21 μM, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…313 The Rhizophora apiculata root endophyte Aspegillus candidus contained seven p-terphenyls, asperterphenyllins A-F 816-822. 316 Asperterphenyllin A exists as a racemic mixture of atropisomers. Another Aspergillus sp.…”
Section: Fungi From Mangrovesmentioning
confidence: 99%
See 2 more Smart Citations
“…313 The Rhizophora apiculata root endophyte Aspegillus candidus contained seven p-terphenyls, asperterphenyllins A-F 816-822. 316 Asperterphenyllin A exists as a racemic mixture of atropisomers. Another Aspergillus sp.…”
Section: Fungi From Mangrovesmentioning
confidence: 99%
“…326 Mangrove sediment-derived Trichoderma atroviride was the source of the simple cyclopentenone acrylic acid derivatives trichodermacid A 864, and trichodermesters A 865 and B 866, 327 while the related cyclopentanes 867 and 868 were reported from Aspergillus avipes isolated from the pneumatophores of Acanthus ilicifolius. 328 All new mangrove fungal-derived MNPs were tested in a variety of assays but only asperterphenyllin G 822 was moderately cytotoxic, 316 penipyrol C 854 showed weak regenerative b-cell effects in zebra sh, 325 and aceneoherqueinone A 849 showed weak inhibition of acetyl choline esterase. 323 All of the other new MNPs were inactive in the assays they were tested in.…”
Section: Fungi From Mangrovesmentioning
confidence: 99%
See 1 more Smart Citation
“…SYSU-SK-7 yielded colletotric A ( 46 ) and colletotric B ( 47 ) and also showed weak cytotoxicity against MAD-MB-435 and A549 cells, with IC 50 values from 16.82 to 37.73 μM [ 39 ]. Seven newly reported prenylated p-terphenyls ( 48 – 54 ) derived from A. candidus LDJ-5 were discovered to possess inhibitory properties against a variety of human cancer cell lines, with IC 50 values ranging from 0.9 to 29.7 μM [ 40 ].…”
Section: Sources Structures and Anti-tumor Activities Of Secondary Me...mentioning
confidence: 99%
“…Furthermore, prenylterphenyllins F ( 2 ), H ( 4 ), J ( 6 ) and prenylcandidusins G ( 10 ) demonstrated cytotoxic activity against 10 human cancer cell lines: HCT‐116, L‐02, BEL‐7402, MGC‐803, A549, HeLa, U87, SH‐SY5Y, HL‐60 and K562, using adriamycin as positive control. The results indicated that prenylterphenyllins H ( 4 ) showed the best activities against the HeLa, A549, MGC‐803, SH‐SY5Y, HCT‐116 and L‐02 cell lines with IC 50 values of 2.0, 0.4, 0.7, 0.6, 0.5 and 3.5 μmol l −1 , respectively (Zhou et al 2020b).…”
Section: Introductionmentioning
confidence: 99%